2000
DOI: 10.1246/cl.2000.76
|View full text |Cite
|
Sign up to set email alerts
|

Non-Contact Measurement of Adsorbed Cytochrome c with Optical Waveguide Spectrometry; The Effect of Distance between Waveguide and Protein on the Spectral Sensitivity

Abstract: Optical waveguide spectrometry with non-contact conditions was performed with the aim of widening the choice of substrate material. The visible absorption spectrum of cytochrome c (cyt.c) adsorbed on a quartz glass or gold surface was detected with the evanescent wave from a co-faced waveguide. A clear correlation was observed between absorbance of cyt.c and the gap between the waveguide surface and the protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The absorbance at 409 nm after subtracting the base line was 0.031 when latex beads with diameter of 120 nm were used. This value approximately agreed with that of cyt.c adsorbed on a quartz glass (0.024) [14] estimated under the same condition such as the number of reflection, gap distance and so on. To analyze the redox activity of cyt.c adsorbed on the ITO electrode, the potential was applied to the noncontact cell system.…”
Section: Spectroscopic Analysis Of the Adsorbed Cytochrome C On The Esupporting
confidence: 86%
See 1 more Smart Citation
“…The absorbance at 409 nm after subtracting the base line was 0.031 when latex beads with diameter of 120 nm were used. This value approximately agreed with that of cyt.c adsorbed on a quartz glass (0.024) [14] estimated under the same condition such as the number of reflection, gap distance and so on. To analyze the redox activity of cyt.c adsorbed on the ITO electrode, the potential was applied to the noncontact cell system.…”
Section: Spectroscopic Analysis Of the Adsorbed Cytochrome C On The Esupporting
confidence: 86%
“…It was revealed that the OWG spectrum of the molecules adsorbed on the substrate, which is not in contact with the waveguide surface, could be detected when the gap is properly controlled. In a previous article, we determined the relation between the absorbance of the spectrum and the gap between the target substrate and the waveguide [14]. Latex beads with appropriate diameter were found to be effective as the gap controller.…”
Section: Introductionmentioning
confidence: 99%
“…13 It was also reported that a redox reaction on the electrode surface can be detected dynamically, while not being affected by diffusion. 14,15 We have proposed a non-contact OWG spectroscopy as a powerful technique to analyze molecules on various surfaces, even opaque substrates. 13 Moreover, OWG spectrometry is expected to be simultaneously collaborated with fluorescence spectra.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of OWG spectroscopy with electrochemical methods can give even better information [21][22][23][24][25]. OWG spectroelectrochemistry is useful technique for sensitive and simple analysis of redox reaction of molecules dissolved in a small amount of solution [22] or adsorbed on opaque electrodes [23,24]. Figure 7.2 shows the spectral change due to the redox reaction of Methylene blue.…”
Section: Introductionmentioning
confidence: 99%